HANDGRIP STRENGTH IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Sandhu Gill, Parminder Kaur; Sandhu, Ravneet; ., Dimple; Dhillon, Sukhjinder Kaur; Arora, Anterpreet Kaur (Pakistan Journal of Physiology, 2016)
Background: Diabetes mellitus type 2 is the most common endocrine disorder all over the world and is characterised by abnormal metabolic conditions and many long term illnesses. Muscle weakness has been linked with type-2 diabetes, even amongst subjects with high body mass indices. There is decremental effect of diabetes mellitus type 2 on skeletal muscles. This study was undertaken to measure the handgrip strength in type-2 diabetic patients as a measure of sarcopenia, and compare it with age- and sex-matched apparently healthy non-diabetic subjects. Method: This comparative cross-sectional study was carried out in the Outpatient Department of Civil Hospital, Amritsar. The study included 50 clinically diagnosed diabetic male patients of more than 50 years age having type-2 diabetes mellitus for at least 10 years; and 50 age- and sex-matched apparently healthy non-diabetic controls. Hand Grip Strength (HGS) of all subjects was measured using Jamar Handheld Dynamometer. The independent t-test was used to analyse the difference in HGS between the diabetic and the non-diabetic subjects. Results: The mean age of study subjects was 54.74±2.61 years, and their mean Body Mass Index (BMI) was 26.83±2.49 Kg/m2. Mean HGS of dominant hand of diabetic and control group was 20.76±3.55 Kg and 32.90±7.60 Kg respectively. HGS of dominant hand amongst diabetic group was significantly lower as compared to controls (t=10.23, p<0.001). Conclusion: Handgrip strength was lower in diabetic patients compared to controls. Pak J Physiol 2016;12(2):19–21